Situation Report: Bulgaria, 28 April 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Lachezar Avramov Dismissed from Government Date for Elections Fixed Intellectuals' Dissent in Bulgaria Foreign Ministry Delegation in Belgrade Bulgarian Comment on China's Opening to the West